A differential PCR assay for the detection of c-erbB 2 amplification used in a prospective study of breast cancer. Issue 5 (October 1997) - Jennings, B A; Hadfield, J E; Worsley, S D; Girling, A; Willis, G
Abstract : AIMS: To establish a robust differential polymerase chain reaction (PCR) assay for the detection of c-erbB 2 amplification in breast cancer that can be used in a routine pathology laboratory. Once established, the assay was used in a prospective study of breast tumours to investigate the relation between c-erbB 2 amplification and both recognised prognostic features and short term clinical outcome. METHODS: The differential PCR was used for the co-amplification of c-erbB 2 and a reference gene from 48 tumour DNA samples and control DNA samples. The ratio of the two genes was determined by image analysis of the PCR products electrophoresed on a highly resolving agarose gel. RESULTS: The differential PCR assay was shown to be accurate and reproducible using the conditions outlined. Twenty six per cent of the breast cancer patients were shown to have c-erbB 2 amplification in their tumour biopsies. Twenty eight per cent of the patients died of their disease or had disease recurrence during the follow up period and 73% of these patients had amplification of c-erbB 2. CONCLUSIONS: A significant association was found between c-erbB 2 amplification and early disease recurrence. This assay could be used to provide a marker for poor prognosis in breast cancer.